Intergrasi akuntansi manajemen dalam strategi perusahaan untuk mendukung tujuan pembangunan berkelanjutan di Indonesia - Ismanda kus adi nugraha; Ajeng Tita Nawangsari (AKUNTANSI 45, 2026)
This research aims to analyze the role and integration of management accounting in corporate strategies to support the achievement of the Sustainable Development Goals (SDGs) in Indonesia. The approach used is a qualitative descriptive literature study with data sources from scientific journals, books, government reports, and academic publications related to sustainable management accounting, environmental accounting, and corporate social responsibility (CSR). The results show that management accounting plays an important role in helping companies achieve a balance between economic, social, and environmental aspects through the application of the Triple Bottom Line (TBL) concept. The integration of environmental accounting in the company's management system has been proven to improve operational efficiency, transparency, eco-friendly product innovation, and the company's reputation in the eyes of stakeholders. In addition, CSR that is integrated with the principles of the SDGs and accounting-based sustainability reporting helps companies realize more measurable and strategic social responsibility. Overall, this study confirms that sustainable management accounting is not only a financial recording and reporting tool, but also a strategic instrument that supports corporate decision-making and policies in achieving sustainable development. The implementation of Environmental, Social, and Governance (ESG) principles supported by a good management accounting system is expected to encourage the Indonesian business world towards more responsible, transparent, and globally competitive business practices.